YbF3/SiO2 Fillers as Radiopacifiers in a Dental Adhesive Resin - Carreño, Neftali L. V.; Oliveira, Thiago C. S.; Piva, Evandro; Leal, Fernanda B.; Lima, Giana S.; Moncks, Marcelo D.; Raubach, Cristiane W.; Ogliari, Fabr´ıcio A. (Nano-Micro Letters, 2012)
The objective of this study was to evaluate the effect of functionalizing a dental adhesive resin with YbF3/SiO2 fillers for use as radiopacifiers. Particles of YbF3/SiO2 were obtained with the high-energy mechanical milling method and characterized by both physical and chemical methods. After characterization, the particles were sieved and silanized prior to being incorporated into an adhesive resin. The stability of the particle suspension was then evaluated. After light activation, the radiopacity, degree of conversion, flexural strength and elastic modulus were determined. The dental adhesive resins with 10 and 15 wt% of filler provided satisfactory radiopacity, while flexural strength and elastic modulus were not affected. The degree of conversion was statistically lower than that of the control (p<0.05). The method used for incorporating the tested ytterbium fluoride/silicon dioxide particles at concentrations of 10 and 15 wt% was shown to be feasible for the development of a radiopaque dental adhesive system.